Jeff Koons : a retrospective - Koons, Jeff, 1955-; Rothkopf, Scott, 1976-; Whitney Museum of American Art; Centre Georges Pompidou; Museo Guggenheim Bilbao (New York : Whitney Museum of American Art, 2014)
Examining the breadth and depth of thirty-five years of work by Jeff Koons (born 1955), one of the most influential and controversial artists of the 20th century, this volume features all of his most famous pieces. In an overview essay, Scott Rothkopf carefully examines the evolution of Koons's work and his development over the past thirty-five years, offering a scholarly perspective on the artist's multi-faceted career.
Foreword / Adam D. Weinberg -- No limits / Scott Rothkopf -- Inflatables -- Pre-new/The new -- Equilibrium -- Luxury and degradation -- Statuary/Kiepenkerl -- Banality -- Made in heaven -- Celebration -- Easyfun -- Easyfun-ethereal -- Popeye -- Hulk Elvis -- Antiquity -- Gazing ball -- York to New York / Jeffrey Deitch -- Love and basketball / Pamela M. Lee -- Happy hour, or How I learned to stop worrying and love the message / Rachel Kushner -- Life as a resource : mythologization, self-marketing, and the creation of value in the work of Jeff Koons / Isabelle Graw -- The gift of art / Achim Hochdorfer -- Designs for living / Antonio Damasio -- Objects that are only boundaries / Alexander Nagel -- One of a kind / Michelle Kuo.
Published on the occasion of an exhibition held at the Whitney Museum of American Art, New York, June 27-Oct. 19, 2014, at Centre Pompidou, Paris, Nov. 26, 2014-Apr. 27, 2015, and at the Guggenheim Museum, Bilbao, Summer 2015.
Includes bibliographical references (pages 253-271) and index.
Keywords: Koons, Jeff, -- 1955- -- Exhibitions